1986
DOI: 10.1007/bf00057694
|View full text |Cite
|
Sign up to set email alerts
|

The meiotic behaviour of the XY pair in Lutreolina crassicaudata (Marsupialia: Didelphoidea)

Abstract: The meiotic behaviour of the XY pair of the didelphid Lutreolina crassicaudata is analyzed by microspreading of spermatocytes for visualization of chromosomal axes and by three-dimensional reconstruction of spermatocyte nuclei from EM thin sections. The delay in pairing of sex chromosomes compared to autosomes and the absence of a synaptonemal complex between the axes of the X and Y chromosomes, already described for South American marsupials by three-dimensional reconstruction and for Australian species with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
3
12
0
Order By: Relevance
“…. The location of AE and CA proteins on the sex chromosomes in male marsupials is consistent with this deviates from that of most eutherian species (Solari and Bianchi 1975;Sharp 1982;Roche et al 1986; Seluja model. Therefore, AEs and CAs should be considered as different structures, and more significantly, they could be et al.…”
Section: Specific Phosphorylation Of Sex Chromosomal Aessupporting
confidence: 70%
See 2 more Smart Citations
“…. The location of AE and CA proteins on the sex chromosomes in male marsupials is consistent with this deviates from that of most eutherian species (Solari and Bianchi 1975;Sharp 1982;Roche et al 1986; Seluja model. Therefore, AEs and CAs should be considered as different structures, and more significantly, they could be et al.…”
Section: Specific Phosphorylation Of Sex Chromosomal Aessupporting
confidence: 70%
“…We found that SCP3 and the cohesin subunits STAG3 and SMC3 recruitment of components of the CE of the SC and A series of morphological and genetic studies have revealed that the orders Didelphimorphia and Paucituberculata to which T. elegans and R. raphanurus, respectively, belong, are the most basal groups within marsupials (Szalay 1994;Amrine-Madsen et al 2003;Nilsson et al 2003). As for D. gliroides, it has been repeatedly claimed that, in spite of its South American distribution, this species is more closely related to Australian marsupials (Kirsch et al 1991;Szalay 1994;Spotorno et al 1997;Palma and Spotorno 1999;Janke et al 2002;Amrine-Madsen et al 2003;Nilsson et al 2003). Taken together, such relationships give support to the idea that the special features that sex chromosomes present during meiosis could have originated very early in the evolution of marsupials [stemming at least from the radiation of the extant marsupial orders 64 million years ago (Nilsson et al 2003)], and they would have been line in some marsupial species (Hayman 1990;Palma 1995), including D. gliroides (Gallardo and Paterson 1987).…”
Section: Specific Phosphorylation Of Sex Chromosomal Aesmentioning
confidence: 99%
See 1 more Smart Citation
“…In most marsupial species, sex chromosomes do not possess a PAR and sex chromosomes do not synapse at all. Instead, they develop a specific structure, called dense plate, which maintains their association (Solari and Bianchi 1975;Sharp 1982;Roche et al 1986;Seluja et al 1987). This structure is formed by the modification of sex chromosomal AEs, which expand on the nuclear envelope giving rise to a dishlike structure in which the ends of the X and Y AEs are immersed (Fig.…”
Section: Marsupial Sex Chromosomal Aes Expand At Their Ends To Form Amentioning
confidence: 99%
“…However, little attention has been paid to the meiotic structure and behaviour of sex chromosomes in the other mammalian taxa, the monotremes and the marsupials. There is only one report on monotreme meiosis (Murtagh, 1977), whereas the meiosis of only some American and Australian marsupial species has been thoroughly described (Koller, 1936;Solari and Bianchi, 1975;Pathak et al, 1980;Sharp, 1982;Roche et al, 1986;Seluja et al, 1987). Some of the features found in eutherian males are also observed in marsupial males.…”
Section: Introductionmentioning
confidence: 99%